Pozzolanic reactivity of chemically pre-treated palm oil clinker powder (POCP) with hydrochloric acid - Amalina Hanani, Ismail (2019)
Revolutionary act on modern cement production is marking a positive finding on the utilization of industrial solid waste and agro-based waste as cement replacement material (CRM) which is rich in silica (SiO2) and alumina (Al2O3). Palm oil wastes are commonly dumped and abandoned in the vicinity due to an improper waste management and could become a serious threat to the environment through the potential risk of pollution. One of its by-product i.e. palm oil clinker (POC) is not a favourable choice as a filler and replacement material for cement in concrete production due to its coarse form, low surface area, and less reactivity. Besides, POC contains impurities of organic carbon and traces of alkali metal oxides and several transition elements, which could inhibit the reaction of Si precursors with Portlandite during hydration process. This study investigated the method of improving the pozzolanic reactivity of POCP through mechanical and chemical pre-treatment. In mechanical pre-treatment, POC was ground to a finer particle passing 300 µm and would be referred as palm oil clinker (POCP) in the main text. Impregnation of POCP particles in hydrochloric acid (HCl) solution was supposed to remove the unburned carbon and unnecessarily elements, besides enhancing the pozzolanic reactivity of the material. However, the optimum parameter for the chemical pre-treatment of POCP has not been fully investigated. Therefore, this research is proposed to investigate the effect of HCl concentration and heating period on the removal of unburned carbon and traces of alkali metals oxides for pre-treatment process. Besides, this study was conducted to analyse the pozzolanic reactivity of chemically pretreated POCP and the performances in cementitious environment. Different combinations of parameters were investigated to obtain the most optimum parameter based on the higher removal of impurities and increment in SiO2 proportion in POCP. The analysis was performed via X-Ray Fluorescence (XRF) analysis. Based on the results, 0.1M – 1h was chosen as the optimum parameter and would be used for the subsequence analysis. Nitrogen adsorption test, particle size distribution, mineralography analysis, and microstructure imaging of POCP were conducted to study the physical characteristic of the source material. Meanwhile, pozzolanic reactivity of POCP was studied via Chapelle test, heat of hydration, and Thermogravimetry analysis. The effect of POCP as a pozzolan was also measured by incorporating it in mortar mixtures. Different percentage of POCP inclusion were adopted and control specimen was used as the benchmark for the entire test. Inclusion of chemically pre-treated POCP in cementitious medium has marked a positive outcome in compressive strength and porosity results. Based on the results, treated 7.5 was chosen as the most applicable POCP replacement for the production of sustainable mortar due to the high strength (27.69 MPa), on par with control mortar. Statistical analysis was conducted to justify the obtained results using mathematical inferences for more solid conclusion and the accuracy of the data sets. According to the statistical analysis for Chapelle method, 0.1 M-1h was compared with 0.5 M-2h on the mean and standard error of the data. 0.1 M-1h has more reliable and consistent data, thus strengthen the decision of using 0.1 M-1h as optimum combination parameter for pretreatment basis. In a nutshell, chemically pre-treat POCP by using optimum parameters (concentration of HCl and heating period) has proven to increase and enhance the pozzolanic reactivity of the material by improving its chemical and physical properties.